First Aeropalynological Survey on the Atmosphere of Sinop, Turkey - Çeter, Talip; Özler, Hülya; Pinar, Nur Münevver (Kastamonu University, 2020)
Aim of study: With this first aeropalynological study in the atmosphere of Sinop, it was aimed to detect seasonal variation of pollen and its relationship with meteorological parameters.
Area of study: This survey was conducted in the atmosphere of the Korucuk district of Sinop.
Material and methods: This study was carried out using Hirst-Burkard 7-day volumetric trap between July 2010 and June 2012.
Main results: During a period of two years, pollen of 61 taxa that included 37 taxa of trees, 23 taxa of other weeds and Poaceae were recorded with the sum of 93,414 pollen grain. Pollen of trees (69.5%) predominantly contributed to the pollen sum followed by Poaceae (17.1%) and other weeds (13.4%).
Highlights: Alnus (2.6%), Amaranthaceae (3.4%), Betula (1.3%), Carpinus (2.6%), Compositae (6.2%), Corylus (23.1%), Cupressaceae (13.7%), Fraxinus (1.7%), Pinaceae (16.1%), Plantago (1.1%), Poaceae (17%) and Quercus (2.2%) were determined as the dominant taxa in the atmosphere. Among the meteorological parameters, temperature and wind speed generally had a positive effect on pollen concentration, while rainfall had a negative effect on it. A pollen calendar was prepared as a result of the pollen grain detected in the atmosphere of Sinop.
Keywords: Sinop; Airborne Pollen; Turkey; Volumetric; Sinop; Airborne Pollen; Volumetric; Pollen Calendar; Turkey; Pollen Calendar; Sinop; Atmosferik Polen; Volumetrik; Polen Takvimi; Türkiye; 2. Zero hunger; 15. Life on land; 13. Climate action; 11. Sustainability